Feature Papers of Water Resources Management, Policy and Governance - Loukas, Athanasios; Garrote, Luis (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Water resource management includes the consideration of all disciplines of hydrology and water sources. Water supplies are allocated and diverted to cover the water needs of a range of agricultural, municipal, industrial, hydro-electrical, and ecological water uses. These water uses are, usually, very competitive, as the available water resources are limited and it is not possible to cover the total water needs in a basin, requiring the setting of water use priorities to best serve societal and ecological needs. To manage the water resources and waterworks may, sometimes, lead to confrontational deliberations and negotiations. As a result, water resource management is one of the world's greatest challenges due to competition for limited resources, regional disparities in water supply and affluence, mounting global water demand, aquifer depletion, and pollution- and climate-change-induced water stress. Proper policy and governance for sustainable water resource management is essential and require new fresh ideas, innovation, and international cooperation. This book includes seven papers by invited renowned researchers and engineers to cover issues of water resource management, governance, and policy. These issues include the following topics: Integrated water resource management; Water resource systems and water availability; National and international water policy, institutional arrangements, and water law; Water conflict resolution, public participation, and decision making; Water resource management, policy and governance in socially and environmentally sensitive areas and regions.